Optimization of power load for the power distribution in the smart grids - Chen, Su. (2013)
The Smart Grid (SG), is regarded as the next generation power grid,which uses two-way flows of electricity and information to create a widely distributed and automated energy delivery network. In this report, we focus our efforts to investigate the optimization problem of load dispatch contract decision with wind power and vehicle to grid (V2G) system integration. Our project considers a problem that a grid operator, a wind power station and a conventional power station have to decide the a contract amount of electricity supplied to the power grid to minimize the cost in the perspective of wind station. From the contract amount, grid operator can approximately know how much electricity would be supplied in the next time period T. It is advantageous for the grid to regulate the frequency and avoid risk of overproduction. V2G system has been considered as the energy storage to store the excess power for future use. An optimization problem for the load dispatch system is formulated to maximize the profit of the wind power station . The solutions of the optimization problem and numerical results is also given .